Rational design of SiBCN microstructures using direct photolithography of patternable preceramic photoresists. (November 2022) - Hanniet, Quentin; Petit, Eddy; Calas-Etienne, Sylvie; Etienne, Pascal; Aissou, Karim; Gervais, Christel; Miele, Philippe; Charlot, Benoit; Salameh, Chrystelle
Graphical abstract: Highlights: Crack-free SiBCN microparts (20–200 µm) are obtained by direct photolithography of molecularly designed boron-containing photocurable preceramic polymers. Surface roughness below 3 nm and Young's modulus of ∼ 60 GPa attest the high quality of SiBCN patterns and pave the way to applications in microfabrication and microfluidics. Abstract: Non-oxide ceramic MEMS based on Si, C, N and B elements are of great importance for high-temperature applications in harsh and oxidizing conditions including electronics, photonics and actuators. Yet, structuring and patterning ceramics is challenging and often relies on conventional soft-lithography or molding processes that can introduce defects and cracks leading to a decrease in the device's performance. Herein, we report on the design for the first time of SiBCN ceramic micro-components (in the 20–200 µm range) from direct patterning of "tailor-made" UV-curable boron-modified polyvinylsilazane preceramic (polyborovinylsilazane) resins. This approach first involves a two-step chemical synthesis of patternable preceramic polymers through acrylate or methacrylate grafting onto polyborovinylsilazane followed by subsequent crosslinking under UV light. FTIR and NMR spectroscopies confirmed the successful grafting of boron and photocurable units on the preceramic polymers while thermogravimetric analysis was used to monitor the polymer-to-ceramic conversion. SiBCN micro-objects obtained after pyrolysis were thoroughly characterized by SEM, AFM, nanoindentation and profilometry techniques. The Young's modulus results for such microstructures (∼60 GPa) are characteristic of good mechanical properties making these ceramic microstructures promising materials for MEMS applications.